Health profile of school children of two schools in Palghar district, western Maharashtra, India - Kakeri, Meena; Howal, Prashant V.; Chaudhari, Yasmeen F. (International Journal Of Community Medicine And Public Health, 2018)
Background: Healthy childhood is basis for healthy and productive adult life. Mortality in school age children is low but morbidity and physical defects constitute major problems. With this background the present comparative study was conducted to explore the nutritional and morbidity patterns among government run primary school children and private school children in Palghar district, Maharashtra. Methods: A descriptive cross-sectional study was conducted during March 2018 in both government school and other private school. Total 400 children studying in class 1 to 4 were included. A pre-designed and pretested questionnaire was used during the interview and clinical examination was carried out to study nutritional status and morbidity pattern among the school children. Results: Out of 400 children, 61 (15.25%) were underweight, 82 (20.5%) were stunted, and 8 (2.0%) were obese. Dental caries was commonest morbidity (55.25%). Two study subjects (1.0%) had suspect cardiac problems. Conclusions: Under-nutrition and morbidities are prevalent in present study. Periodic complete health evaluation should be planned for early diagnosis of nutritional and morbid health problems.